"Lockeian liberalism" and "classical republicanism": the formation, function and failure of the categories. Issue 1 (2nd January 2023) - Clark, J. C. D.
ABSTRACT: The contest between "Lockeian liberalism" and "classical republicanism" as explanatory frameworks for the intellectual history of the American Revolution, and therefore of the present-day United States, has been one of the longest running and most distinguished in recent U.S. historiography. It also has major implications for the history of political thought in the North Atlantic Anglophone world more widely. Yet this debate was merely suspended when it was held to have ended in an ill-defined compromise. Although some U.S. historians expressed doubts and qualifications, attention in U.S. historiography moved on to other themes while leaving the initial problem unsolved. This article reopens the question; it suggests that a historicization of both these two categories is now both possible and necessary, and that their supersession will advance understanding of the Revolution. It seeks to help solve this problem by the same means that the debate began: that is, by re-establishing a link between U.S. and U.K. historiographies.